Remote working pre- and post-COVID-19: an analysis of new threats and risks to security and privacy - Nurse, Jason R. C.; Williams, Nikki; Collins, Emily; Panteli, Niki; Blythe, John; Koppelman, Ben (Springer, 2021)
COVID-19 has radically changed society as we know it. To reduce the spread of the virus, millions across the globe have been forced to work remotely, often in make-shift home offices, and using a plethora of new, unfamiliar digital technologies. In this article, we critically analyse cyber security and privacy concerns arising due to remote working during the coronavirus pandemic. Through our work, we discover a series of security risks emerging because of the realities of this period. For instance, lack of remote-working security training, heightened stress and anxiety, rushed technology deployment, and the presence of untrusted individuals in a remote-working environment (e.g., in flatshares), can result in new cyber-risk. Simultaneously, we find that as organisations look to manage these and other risks posed by their remote workforces, employee’s privacy (including personal information and activities) is often compromised. This is apparent in the significant adoption of remote workplace monitoring, management and surveillance technologies. Such technologies raise several privacy and ethical questions, and further highlight the tension between security and privacy going forward.
Human-Computer Interaction International 2021 (HCII 2021)
Keywords: Remote working; Working from home; Coronavirus; Cyber security; Privacy; Human Factors; Workplace surveillance; Ethics; Human Computer Interaction